"Language and the Periphery" Response to Book Forum on Insurgent Imaginations: World Literature and the Periphery. (September 2022) - Majumder, Auritro
Abstract: Auritro Majumder is Associate Professor of English at University of Houston. He is the author of Insurgent Imaginations: World Literature and the Periphery (Cambridge University Press, 2021) and currently chair of the South Asian and Diasporic Languages, Literatures and Cultures forum of the Modern Language Association.